Challenge and Opportunities: A Qualitative Exploration of Junior High School English Language Educators' Perspectives on Implementing Differentiated Instruction - Rahmaniar Rahmaniar; Zulkifli Surahmat; Ahmed Sardi; Ihfa Indira Nurnaifah (JELITA, 2024)
The article explores the implementation of Differentiated Instruction (DI), focusing on the challenges and opportunities faced by English language teachers in junior high schools. The study follows a qualitative approach within a social constructivist worldview, emphasizing the need for tailored strategies to address diverse learning needs. The research questions delve into teachers' perceptions of DI, the challenges encountered, and effective strategies for addressing diversity in the classroom. The proposed strategies reflect a systematic approach to address challenges in differentiated learning. Through team teaching, technology integration, and enhanced knowledge mapping, the study aims to contribute valuable insights into the perspectives of English as a Foreign Language (EFL) teachers on DI. The findings anticipate informing support mechanisms for teachers to meet the diverse needs of their students effectively.